SWOT Analysis of Surya Utama Building Store in Batam City - Nilla Kuntalawati, Cindy Nabilla; Harlan, Fandy Bestario (Journal of Collaborative Industrial Management (JCIM), 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by Surya Utama Building Store in competing within the building materials business in Batam City. The method used is a descriptive qualitative approach with data collection techniques through interviews, observations, questionnaires, and documentation. Data analysis was conducted using IFAS and EFAS matrices to assess the company’s internal and external factors. The results show that the store’s main strengths lie in its strategic location, product quality, and good service, although it still faces weaknesses such as conventional promotion and limited capital. Externally, the store has opportunities from government regulatory support and infrastructure development, but it also faces threats from competitors who are more active in promotion and price wars. The store’s strategic position is in quadrant I (aggressive), indicating that growth strategies can be optimized by leveraging strengths to seize market opportunities. This study recommends enhancing digitalization, reorganizing the store, strengthening human resources, and adopting technology-based promotional strategies to improve competitiveness and business sustainability.